SELF-DEVELOPMENT AND PSYCHOHYGIENE IN EDUCATION OF NURSES AND SOCIAL WORKERS (WE LEARN THEM TO CARE NOT ONLY ABOUT THE CLIENT?) - Guľašová, M. (Україна. Здоров’я нації, 2023)
The aim of the paper is to point out the need of education in the field of psychohygiene among students in helping professions. The place of health psychology in the training of future professionals is increasing in the context of primary prevention. Neglect of psychohygiene is related to reduced quality of life, job satisfaction and psychological safety at work. The correlation of deficiencies in the above components with burnout is significant. Professional personality requirements are subject to change in society and require high professional standards, professional competence, human and moral qualities.